Kepribadian Dan Perubahan Organisasi: Mengelola Respon Individu Terhadap Perubahan dalam Lingkungan Kerja - Ahmad Munfarih Fadhil; Hilyatul Muzahrofah; Selnistia Hidayati (Jurnal Konseling dan Psikologi Indonesia, 2026)
This study examines the relationship between individuals’ personal characteristics and their responses to structural transformations in professional contexts. Drawing on theoretical frameworks of personality, such as the Big Five model, the paper explores how attributes like openness to new experiences and emotional stability contribute to individuals’ adaptive capacity. To reduce barriers and optimize work outcomes, the discussion also addresses methods for managing personal responses, including effective dialogue and competency development programs. This review is based on an evaluation of recent scientific publications from the 2020-2024 period and highlights the importance of strategies that take personality profiles into account to ensure the smooth implementation of institutional change.